Iron-modified molybdenum disulfide-based piezoelectric catalytic material as well as preparation method and application thereof

Through the combination of iron-modified molybdenum disulfide-based piezoelectric catalytic material and ultrasonic induced, piezoelectric catalysis and Fenton-like reactions, the problem of poor removal of norfloxacin in the prior art was solved, efficient pollutant removal was achieved, and the advantages of low energy consumption and low economic cost were achieved.

CN119500192AActive Publication Date: 2025-02-25SHANDONG UNIV

Patent Information

Application Number
CN202411664746.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The prior art removes residual norfloxacin in the water environment, and requires the addition of additional chemicals or relies on fixed reaction conditions, resulting in waste of resources and ineffective catalytic effects.

Method used

By using iron-modified molybdenum disulfide-based piezoelectric catalytic material for electrocatalytic degradation, piezoelectric catalysis and Fenton-like reaction are coupled, hydrogen peroxide is effectively utilized and catalytic effect is improved.

Benefits of technology

Under ultrasonic induction, iron-modified molybdenum disulfide-based piezoelectric catalytic material can achieve a removal rate of norfloxacin of 95.7% within 15 minutes, and the preparation process is simple, energy consumption is low and economical cost is low.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500192A_ABST
    Figure CN119500192A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-modified molybdenum disulfide-based piezoelectric catalytic material and a preparation method and application thereof.The preparation method comprises the following steps that ammonium molybdate and thiourea are mixed with water in proportion, and then a mixed solution is subjected to a hydrothermal reaction; drying the solution after the hydrothermal reaction to obtain molybdenum disulfide; molybdenum disulfide and a ferric iron salt solution are mixed and stirred, and then a reducing agent is added for reduction; and collecting and drying the reduced solution to obtain the iron-modified molybdenum disulfide-based piezoelectric catalytic material. A piezoelectric catalysis system of molybdenum disulfide can be more effectively utilized to generate hydrogen peroxide in situ, and Fenton-like reaction is carried out, so that pollutants are better removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to an iron-modified molybdenum disulfide-based piezoelectric catalytic material and a preparation method and application thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Removing new pollutants from the environment has received widespread attention recently. Antibiotics are widely used in all aspects of human production and life. Antibiotics that are not metabolized by organisms and residual antibiotics entering water have become a new type of pollutant that affects water quality. Among them, fluoroquinolone antibiotics have good antibacterial effects, but they have a long residual time and are not easy to degrade, resulting in a large amount of accumulation in water and conversion into toxic substances, posing a serious threat to the earth. Norfloxacin is a third-generation drug of fluoroquinolone antibiotics and a broad-spectrum antibacterial drug that has been widely used to treat many infections caused by antibiotic-resistant bacteria. In order to remove residual norfloxacin in water environments, commonly used treatment methods include biological methods, physical techniques, and chemical methods. However, these traditional technologies still have certain disadvantages, such as poor removal of pollutants, the need to add additional chemical agents, or reliance on fixed reaction conditions. Therefore, it is crucial to develop new and effective methods to eliminate antibiotics in aquatic environments.

[0004] The piezoelectric effect is actually a physical phenomenon. The crystal structure of a piezoelectric material with an internal polarization field deforms when subjected to an applied external stress, and the surface charges separate and generate a piezoelectric potential, thereby generating an internal electric field within the material. The piezoelectric potential generated by the external force enhances the separation of free carriers and promotes the chemical reaction process. This phenomenon is called piezocatalysis, which is the conversion of mechanical energy into chemical energy. Piezocatalytic degradation refers to the spontaneous polarization and piezoelectric potential generated by the piezoelectric nanomaterial when mechanical stress (such as stirring or ultrasonic vibration) is applied to the piezoelectric nanomaterial, driving the carrier to move in the opposite direction in the piezoelectric nanomaterial, reacting with adsorbed water and oxygen to form active oxygen species, and then mineralizing and decomposing organic pollutants through redox reactions.

[0005] Compared with common three-dimensional piezoelectric materials such as zinc oxide and barium titanate, two-dimensional layered nanomaterials are more ideal, with ultra-thin layered structures, easier deformation, and the ability to withstand large strains. The high piezoelectric properties of two-dimensional transition metal sulfides have been theoretically verified, and they have been found to have high piezoelectric coefficients in experimental studies. Molybdenum disulfide is widely used in catalytic degradation of pollutants due to its abundant reserves, direct preparation methods, high chemical stability, and diverse physical and chemical properties. The use of molybdenum disulfide as a piezoelectric catalyst can generate hydrogen peroxide in situ during the catalytic reaction. However, the hydrogen peroxide produced in the piezoelectric catalytic system has not been effectively utilized, resulting in a waste of resources, and the catalytic effect of the piezoelectric catalytic system is not effective enough. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide an iron-modified molybdenum disulfide-based piezoelectric catalytic material and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing an iron-modified molybdenum disulfide-based piezoelectric catalytic material, comprising the following steps:

[0009] ammonium molybdate and thiourea are mixed with water in a certain proportion, and then the mixture is subjected to a hydrothermal reaction;

[0010] Drying the solution after the hydrothermal reaction to obtain molybdenum disulfide;

[0011] Molybdenum disulfide and a trivalent iron salt solution are mixed and stirred, and a reducing agent is added thereto for reduction;

[0012] The reduced solution is collected and dried to obtain the iron-modified molybdenum disulfide-based piezoelectric catalytic material.

[0013] The present invention uses exogenous metal element ferrous ions to modify molybdenum disulfide, and the prepared Fe-MoS2 has more sensitive inherent piezoelectric properties. In the catalytic degradation process, molybdenum disulfide as a piezoelectric catalyst can generate hydrogen peroxide in situ during the catalytic reaction process. Since Fe or Mo ions react quickly to consume the hydrogen peroxide generated in situ, a Fenton-like reaction is carried out, so that the generated hydrogen peroxide is effectively utilized, and better removal of pollutants is achieved.

[0014] In some embodiments, the molar ratio of ammonium molybdate to thiourea is 1.5-2.5:30-60.

[0015] Preferably, the molar ratio of ammonium molybdate to thiourea is 2:50.

[0016] In some embodiments, the temperature of the hydrothermal reaction is 180-220° C., and the time of the hydrothermal reaction is 20-30 h.

[0017] Preferably, the temperature of the hydrothermal reaction is 200° C., and the time of the hydrothermal reaction is 24 h.

[0018] In some embodiments, the dried molybdenum disulfide is washed with water and anhydrous ethanol in sequence. Unreacted ionic substances are washed with water; possible organic substances are washed with ethanol; and the materials are washed with water and ethanol to ensure that the materials are pure and free of impurities.

[0019] Preferably, the method further comprises the step of drying the cleaned molybdenum disulfide.

[0020] In some embodiments, the molar ratio of molybdenum disulfide to ferric iron is 1:0.15-1.05.

[0021] In some embodiments, the molybdenum disulfide and the ferric iron salt solution are mixed and stirred for 20-30 hours. The mixing and stirring time is relatively long to ensure that the iron ions are adsorbed on the surface of the molybdenum disulfide.

[0022] In some embodiments, the reducing agent is sodium borohydride, stannous chloride, or potassium borohydride.

[0023] Preferably, the molar ratio of ferric iron to sodium borohydride is 1: 5. Sodium borohydride is added in excess to ensure complete reduction.

[0024] Preferably, after adding the reducing agent, the reaction is stirred for 1 hour.

[0025] In some embodiments, the method further includes washing the prepared iron-modified molybdenum disulfide-based piezoelectric catalytic material with water and anhydrous ethanol.

[0026] In a second aspect, the present invention provides an iron-modified molybdenum disulfide-based piezoelectric catalytic material prepared by the preparation method.

[0027] In a third aspect, the present invention provides the use of the iron-modified molybdenum disulfide-based piezoelectric catalytic material in the electrocatalytic degradation of organic pollutants.

[0028] In some embodiments, the organic contaminant is norfloxacin.

[0029] In a fourth aspect, the present invention provides a piezoelectric catalytic degradation method for norfloxacin, comprising the following steps: placing the iron-modified molybdenum disulfide-based piezoelectric catalytic material into wastewater to be degraded, applying ultrasound, and performing degradation.

[0030] In some embodiments, the frequency of the applied ultrasound is 20 hKz and the power is 90 W.

[0031] The beneficial effects achieved by one or more embodiments of the present invention are as follows:

[0032] The present invention proposes coupling piezoelectric catalysis and Fenton-like reactions, effectively utilizing hydrogen peroxide that may be generated in situ during the piezoelectric catalytic degradation of pollutants, and by means of post-modification, doping iron elements on the surface of molybdenum disulfide to prepare an iron-modified molybdenum disulfide-based piezoelectric catalytic material. Under ultrasonic induction, the catalyst material is used to degrade the antibiotic norfloxacin, achieving a removal rate of 95.7% within 15 minutes (93.2% in 5 minutes).

[0033] The preparation process of the present invention is simple, does not require expensive equipment, has a high preparation yield, uses low power and frequency in the ultrasonic action stage, has low energy consumption, and has low economic cost. It has a bright prospect in the large-scale application of piezoelectric catalytic degradation of pollutants in the future. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] Figure 1 is a SEM image of the iron-modified molybdenum disulfide catalytic material obtained in Example 1;

[0036] Figure 2 The TEM image (a) and element distribution image (b) of the composite catalytic material of the iron-modified molybdenum disulfide catalytic material obtained in Example 1 have obvious thin-layer nanoflowers and uniform distribution of various elements;

[0037] Figure 3 The PFM test diagram (b) of the composite catalyst material of the iron-modified molybdenum disulfide catalyst material obtained in Example 1 shows that the composite catalyst has a higher intrinsic piezoelectric response than the control material (a);

[0038] Figure 4 The specific surface area (a) and pore size distribution (b) of the composite catalytic material of the iron-modified molybdenum disulfide catalytic material obtained in Example 1;

[0039] Figure 5 This is a performance diagram of the piezoelectric degradation of the antibiotic norfloxacin by the iron-modified molybdenum disulfide catalytic material under ultrasound obtained in Example 1;

[0040] Figure 6 This is a performance diagram of the piezoelectric catalytic degradation of norfloxacin by the iron-modified molybdenum disulfide catalytic material obtained in Example 1 under the action of ultrasound and different catalyst dosages.

[0041] Figure 7 This is a performance diagram of the piezoelectric catalytic degradation of norfloxacin by the iron-modified molybdenum disulfide catalytic material obtained in Example 1 under ultrasound and different ultrasound power conditions.

[0042] Figure 8 This is a performance diagram of the piezoelectric catalytic degradation of norfloxacin by the iron-modified molybdenum disulfide catalytic material obtained in Example 1 under ultrasound and different substrate concentrations.

[0043] Fig. 9 This is a performance diagram of the iron-modified molybdenum disulfide catalytic material obtained in Example 2-4 for the piezoelectric catalytic degradation of norfloxacin under ultrasonic action.

[0044] Fig.10 This is a test chart of Example 1 and Comparative Examples 1-4 showing the generation of hydrogen peroxide by the transition metal modified molybdenum disulfide catalytic material under ultrasonic action and piezoelectric catalysis. DETAILED DESCRIPTION

[0045] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0046] The present invention will be further described below in conjunction with the embodiments.

[0047] Example 1

[0048] Add (NH4)2MoO4 (2 mmol) and thiourea (50 mmol) into water and stir for about 10 min to dissolve to obtain a mixed solution;

[0049] The mixed solution was transferred into a 100 ml autoclave and subjected to hydrothermal reaction at 200 °C for 24 h;

[0050] After the reaction is completed, the solution in the reactor is cooled and the solid-liquid separation is performed. The solid is washed with water for 3 times and then with anhydrous ethanol for 3 times. The solid is then dried in a vacuum oven for 12 hours to obtain MoS2.

[0051] Disperse the dried molybdenum disulfide in 160 ml of 6.25 mmol / L ferric nitrate solution, stir thoroughly for 24 hours, then add 0.378 g of sodium borohydride and stir for 1 hour for reduction reaction;

[0052] After the reduction reaction is completed, the solution after the reaction is vacuum dried to obtain the iron-modified molybdenum disulfide piezoelectric catalytic material.

[0053] The prepared iron-modified molybdenum disulfide material was subjected to a piezoelectric effect test, and antibiotics were used as target pollutants to test the piezoelectric catalytic degradation performance of the composite material in degrading pollutants.

[0054] The morphology of Fe-MoS2 was tested by scanning electron microscopy (SEM), and it was observed that the modified material had a smaller nanoflower morphology. Figure 1 .

[0055] From the transmission electron microscope (TEM) test image, it can be found that Fe-MoS2 has a thin layer of nanoflower structure, and the iron element is evenly distributed on the MoS2 substrate, which proves the successful preparation of the modified material. Figure 2 .

[0056] By modifying MoS2 with iron, the specific surface area and pore size of Fe-MoS2 were regulated, that is, the specific surface area increased and the pore size decreased. This improvement promoted the catalytic reaction. Figure 4 .

[0057] In order to further study the piezoelectric properties of the synthesized materials at the nanoscale, the piezoelectric force microscope (PFM) technique was used to test the unmodified MoS2 and Fe-MoS2. The piezoelectric amplitude curve shows that the local deformation of Fe-MoS2 is significantly greater than that of MoS2, and the d33 value of Fe-MoS2 is calculated to be 10 times higher than that of MoS2. The results show that Fe-MoS2 has more sensitive intrinsic piezoelectric properties, which can be seen in detail. Figure 3 .

[0058] Example 2

[0059] Add (NH4)2MoO4 (2 mmol) and thiourea (50 mmol) into water and stir for about 10 min to dissolve to obtain a mixed solution;

[0060] The mixed solution was transferred into a 100 ml autoclave and subjected to hydrothermal reaction at 200 °C for 24 h;

[0061] After the reaction is completed, the solution in the reactor is cooled and the solid-liquid separation is performed. The solid is washed with water for 3 times and then with anhydrous ethanol for 3 times. The solid is then dried in a vacuum oven for 10 hours to obtain MoS2.

[0062] Disperse the dried molybdenum disulfide in 160 ml of 8.75 mmol / L ferric nitrate solution, stir thoroughly for 20 hours, then add 0.529 g of sodium borohydride and stir for 1 hour for reduction reaction;

[0063] After the reduction reaction is completed, the solution after the reaction is vacuum dried to obtain the iron-modified molybdenum disulfide piezoelectric catalytic material.

[0064] Example 3

[0065] Add (NH4)2MoO4 (2 mmol) and thiourea (50 mmol) into water and stir for about 10 min to dissolve to obtain a mixed solution;

[0066] The mixed solution was transferred into a 100 ml autoclave and subjected to hydrothermal reaction at 200 °C for 24 h;

[0067] After the reaction is completed, the solution in the reactor is cooled and the solid-liquid separation is performed. The solid is washed with water for 3 times and then with anhydrous ethanol for 3 times. The solid is then dried in a vacuum oven for 15 hours to obtain MoS2.

[0068] Disperse the dried molybdenum disulfide in 160 ml of 3.75 mmol / L ferric nitrate solution, stir thoroughly for 20 hours, then add 0.2268 g of sodium borohydride and stir for 1 hour for reduction reaction;

[0069] After the reduction reaction is completed, the solution after the reaction is vacuum dried to obtain the iron-modified molybdenum disulfide piezoelectric catalytic material.

[0070] Example 4

[0071] Add (NH4)2MoO4 (2 mmol) and thiourea (50 mmol) into water and stir for about 10 min to dissolve to obtain a mixed solution;

[0072] The mixed solution was transferred into a 100 ml autoclave and subjected to hydrothermal reaction at 200 °C for 24 h;

[0073] After the reaction is completed, the solution in the reactor is cooled and the solid-liquid separation is performed. The solid is washed with water for 3 times and then with anhydrous ethanol for 3 times. The solid is then dried in a vacuum oven for 15 hours to obtain MoS2.

[0074] The dried molybdenum disulfide was dispersed in (160) ml of 1.25 mmol / L ferric nitrate solution, stirred for 20 hours, and then (0.0756) g of sodium borohydride was added and stirred for 1 hour for reduction reaction;

[0075] After the reduction reaction is completed, the solution after the reaction is vacuum dried to obtain the iron-modified molybdenum disulfide piezoelectric catalytic material.

[0076] Comparative Example 1

[0077] The difference from Example 1 is that only iron nitrate is replaced by cobalt nitrate to obtain a cobalt-modified molybdenum disulfide piezoelectric catalytic material.

[0078] Comparative Example 2

[0079] The difference from Example 1 is that only the iron nitrate is replaced by nickel nitrate to obtain the nickel-modified molybdenum disulfide piezoelectric catalytic material.

[0080] Comparative Example 3

[0081] The difference from Example 1 is that only the iron nitrate is replaced by copper nitrate to obtain the copper-modified molybdenum disulfide piezoelectric catalytic material.

[0082] Comparative Example 4

[0083] The difference from Example 1 is that only iron nitrate is replaced by zinc nitrate to obtain zinc-modified molybdenum disulfide piezoelectric catalytic material.

[0084] The catalytic performance of the piezoelectric catalytic materials prepared in Examples 1-4 and Comparative Examples 1-4 was tested.

[0085] Test 1

[0086] 350 ml of a 10 mg / L norfloxacin aqueous solution was prepared and divided into 7 portions, and the iron-modified molybdenum disulfide prepared in Example 1, molybdenum disulfide alone, and 0.01 g of the piezoelectric catalytic material prepared in Comparative Examples 1-4 were added to each portion of the norfloxacin aqueous solution, and an ultrasonic rod was inserted therein; the remaining group was used as a blank control, in which only the ultrasonic rod was inserted without adding the piezoelectric catalyst;

[0087] The ultrasonic rod parameters were set to 90W power and 20 Hz frequency, and samples were collected every 1 min to test the effect of piezoelectric catalysis on the degradation of organic pollutants.

[0088] Norfloxacin was used as the target pollutant to evaluate the piezoelectric catalytic performance. Compared with the modification of other transition metal salts and single ultrasonic action, it was found that Fe-MoS2 had excellent piezoelectric catalytic degradation performance, with a removal rate of 95.7% within 15 minutes (93.2% at 5 minutes). Compared with other materials, it also showed the fastest degradation rate, indicating that iron-modified molybdenum disulfide can significantly improve the piezoelectric catalytic performance. Figure 5 .

[0089] Test 2

[0090] 150 ml of a 10 mg / L norfloxacin aqueous solution was prepared and divided into three portions. The iron-modified molybdenum disulfide prepared in Example 1 was added to each portion of the norfloxacin aqueous solution to give concentrations of 0.1 g / L, 0.2 g / L and 0.3 g / L, respectively. An ultrasonic rod was inserted thereinto, and the ultrasonic rod parameters were set to 90 W power and 20 Hz frequency. Samples were collected every 1 min to test the effect of piezoelectric catalytic degradation of organic pollutants.

[0091] The performance of piezoelectric catalytic degradation of norfloxacin under different catalyst dosage conditions is shown in Figure 6 .

[0092] Test Three

[0093] 200 ml of a 10 mg / L norfloxacin aqueous solution was prepared and divided into 4 portions. The iron-modified molybdenum disulfide prepared in Example 1 was added to each portion of the norfloxacin aqueous solution to a concentration of 0.2 g / L. An ultrasonic rod was inserted thereinto, and the ultrasonic rod parameters were set to 45 W, 90 W, 135 W, and 180 W power and 20 Hz frequency, respectively. Samples were collected every 1 min to test the effect of piezoelectric catalytic degradation of organic pollutants.

[0094] The performance diagram of piezoelectric catalytic degradation of norfloxacin under different ultrasonic power conditions is shown in Figure 7 .

[0095] Test 4

[0096] 50 ml of 5, 10, 15 and 20 mg / L norfloxacin aqueous solutions were prepared, and the iron-modified molybdenum disulfide prepared in Example 1 was added to each norfloxacin aqueous solution to make its concentration 0.2 g / L. An ultrasonic rod was inserted therein, and the ultrasonic rod parameters were set to 90 W power and 20 Hz frequency. Samples were collected every 1 min to test the effect of piezoelectric catalytic degradation of organic pollutants.

[0097] Performance diagram of piezoelectric catalytic degradation of norfloxacin under different substrate concentration conditions, see Figure 8 .

[0098] It can be seen that Fe-MoS2 achieves excellent removal effect under different norfloxacin substrate concentrations, different catalytic dosages, and different ultrasonic powers.

[0099] Test Five

[0100] 200 ml of a 10 mg / L norfloxacin aqueous solution was prepared and divided into 4 portions. The iron-modified molybdenum disulfide prepared in Example 2-4 was added to each portion of the norfloxacin aqueous solution to a concentration of 0.2 g / L. An ultrasonic rod was inserted thereinto, and the ultrasonic rod parameters were set to 90 W power and 20 Hz frequency. Samples were collected every 1 min to test the effect of piezoelectric catalytic degradation of organic pollutants.

[0101] The performance diagram of piezoelectric catalytic degradation of norfloxacin under different molar ratios of molybdenum disulfide and trivalent iron is shown in Fig. 9 .

[0102] Test Six

[0103] The generation of hydrogen peroxide in the catalytic process of different catalysts was tested by iodine titration. The production of hydrogen peroxide was determined by ultraviolet spectrophotometry. 50 ml of 10 mg / L norfloxacin aqueous solution was prepared, and the iron-modified molybdenum disulfide prepared in Example 1 was added to make its concentration 0.2 g / L. An ultrasonic rod was inserted therein, and the ultrasonic rod parameters were set to 90 W power and 20 Hz frequency. Samples were collected every 1 min, and 1.5 ml of 0.1 M potassium iodide solution and 50 μl of 0.01 M ammonium molybdate solution were added to 500 μL of the solution to be tested. After reacting for 15 min, the absorbance value was measured at 352 nm.

[0104] Among them, Fe-MoS2 has the lowest hydrogen peroxide content, which is due to the rapid reaction with Fe or Mo ions to consume the in-situ generated hydrogen peroxide, which also confirms the occurrence of a Fenton-like reaction.

[0105] The generation of hydrogen peroxide by different catalysts during the catalytic process is shown in Fig.10 .

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing an iron-modified molybdenum disulfide-based piezoelectric catalytic material, characterized in that: The steps include: ammonium molybdate and thiourea are mixed with water in a certain proportion, and then the mixture is subjected to a hydrothermal reaction; Drying the solution after the hydrothermal reaction to obtain molybdenum disulfide; Molybdenum disulfide and a trivalent iron salt solution are mixed and stirred, and a reducing agent is added thereto for reduction; The reduced solution is collected and dried to obtain the iron-modified molybdenum disulfide-based piezoelectric catalytic material.

2. The method for preparing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 1, characterized in that: The molar ratio of ammonium molybdate to thiourea is 1.5-2.5:30-60; Preferably, the molar ratio of ammonium molybdate to thiourea is 2:

50.

3. The method for preparing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180-220°C, and the time of the hydrothermal reaction is 20-30h; Preferably, the temperature of the hydrothermal reaction is 200° C., and the time of the hydrothermal reaction is 24 h.

4. The method for preparing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 1, characterized in that: The method comprises the steps of washing the molybdenum disulfide obtained after drying with water and anhydrous ethanol in sequence; Preferably, the method further comprises the step of drying the cleaned molybdenum disulfide.

5. The method for preparing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 1, characterized in that: The molar ratio of molybdenum disulfide to ferric iron is 1:0.15-1.05; Preferably, the molybdenum disulfide and the ferric iron salt solution are mixed and stirred for 20-30 hours.

6. The method for preparing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 1, characterized in that: The reducing agent is sodium borohydride, stannous chloride or potassium borohydride; Preferably, the molar ratio of ferric iron to sodium borohydride is 1:5; Preferably, after adding the reducing agent, the reaction is stirred for 1 hour.

7. The method for preparing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 1, characterized in that: The method also includes the step of washing the prepared iron-modified molybdenum disulfide-based piezoelectric catalytic material with water and anhydrous ethanol.

8. An iron-modified molybdenum disulfide-based piezoelectric catalytic material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.

9. Use of the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 8 in electrocatalytic degradation of organic pollutants; Preferably, the organic pollutant is norfloxacin.

10. A piezoelectric catalytic degradation method for norfloxacin, characterized in that: The method comprises the following steps: placing the iron-modified molybdenum disulfide-based piezoelectric catalytic material according to claim 8 into wastewater to be degraded, applying ultrasound to perform degradation; Preferably, the frequency of the applied ultrasound is 20hKz and the power is 90W.

Citation Information

Patent Citations

  • Method for efficiently removing organic wastewater through molybdenum disulfide catalysis assisted zero-valent iron heterogeneous electro-Fenton

    CN111217429A

  • Preparation method of high-dispersion nickel modified molybdenum disulfide

    CN112694126A

  • Preparation method of Bi-MoS2 nano composite material for electrocatalytic synthesis of ammonia

    CN113215598A

  • Iron-loaded molybdenum disulfide nanosphere catalytic material and preparation method thereof

    CN116037163A

  • Co-coated MoS2 / carbon cloth composite piezoelectric catalyst and preparation method and application thereof

    CN117019177A

Cited By

  • Selenium-doped layered mixed-phase molybdenum disulfide-based piezoelectric catalyst, preparation method and application

    CN121513909A